2017
DOI: 10.1002/chem.201702939
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing [3‐(Dimethylamino)propyl]aluminium(III) Complexes as Novel Atomic Layer Deposition (ALD) Precursors for Al2O3: Synthesis, Characterization and ALD Process Development

Abstract: Identification and synthesis of intramolecularly donor-stabilized aluminium(III) complexes, which contain a 3-(dimethylamino)propyl (DMP) ligand, as novel atomic layer deposition (ALD) precursors has enabled the development of new and promising ALD processes for Al O thin films at low temperatures. Key for this promising outcome is the nature of the ligand combination that leads to heteroleptic Al complexes encompassing optimal volatility, thermal stability and reactivity. The first ever example of the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…[ 67 ] Of course, for the ZnO layers obtained herein, this needs to be proven and is currently under investigation. However, the barrier performance is in the same range as the OTR of equivalently thick Al 2 O 3 layers on PET, as shown earlier for the same polymer substrates, [ 49,50 ] rendering the ZnO layers to be applicable as transparent gas barrier layers (GBLs).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…[ 67 ] Of course, for the ZnO layers obtained herein, this needs to be proven and is currently under investigation. However, the barrier performance is in the same range as the OTR of equivalently thick Al 2 O 3 layers on PET, as shown earlier for the same polymer substrates, [ 49,50 ] rendering the ZnO layers to be applicable as transparent gas barrier layers (GBLs).…”
Section: Resultsmentioning
confidence: 61%
“…Recently we successfully demonstrated that intramolecular stabilized aluminum compounds can potentially substitute trimethyl aluminum (TMA), which is virtually the DEZ equivalent of aluminum precursors. [ 49,50 ] This approach was adapted toward zinc compounds which is the focus of this study for ALD applications. Thus, bis‐3‐( N , N ‐dimethylamino)propyl zinc(II) ([Zn(DMP) 2 ], BDMPZ) was synthesized by introducing the 3‐( N , N ‐dimethylamino)propyl (DMP) ligand which stabilizes the Zn center via a dative bond of the amine, [ 51,52 ] and thoroughly analyzed the compound in terms of its thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR spectra suggest that -CH 3 groups decompose to -CH 2and that C=N bonds are formed, while other decomposition reactions also proceed at or above 250°C. Figure 4 c shows that the masses attributed to -CH 2 -(13, 14, and 15 amu) increase with increasing heating temperature, while the masses associated with methane and methyl ionization (16,17, and 18 amu) decrease with increasing heating temperature. Therefore, these results confirm that both the FT-IR and QMS analyses provide similar results regarding the decomposition reactions of vaporized CpZr(NMe 2 ) 3 .…”
Section: Peak Areasmentioning
confidence: 98%
“…So, thermal decomposition of ligand should occur at process temperature. In order to two conflicting requirements about thermal stability of precursor, many researchers are designing a new structure precursor [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With its self‐limiting growth by sequential half‐cycles, ALD and PEALD processes are capable of producing pin‐hole free and highly conformal thin films. While thermal ALD can be used to deposit many materials already at low temperatures, the adaption of PEALD enables depositions even at room temperature by using highly reactive plasma species which can provide a more efficient deposition in terms of shorter cycle times. The low substrate temperatures are an appealing benefit of PEALD especially within the context of coating sensitive polymers.…”
Section: Introductionmentioning
confidence: 99%